1997
DOI: 10.1016/s0370-2693(97)00691-6
|View full text |Cite
|
Sign up to set email alerts
|

The three-nucleon system near the N-d threshold

Abstract: The three-nucleon system is studied at energies a few hundred keV above the N-d threshold. Measurements of the tensor analyzing powers T 20 and T 21 for p-d elastic scattering at E c.m. = 432 keV are presented together with the corresponding theoretical predictions. The calculations are extended to very low energies since they are useful for extracting the p-d scattering lengths from the experimental data. The interaction considered here is the Argonne V18 potential plus the Urbana three-nucleon potential. The… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
38
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 23 publications
10
38
2
Order By: Relevance
“…A consistent treatment of screening effects is crucial for a stable and reliable theoretical extraction of this quantity. Our result for the quartet pd scattering length, 4 a p-d = (10.9 ± 0.4) fm, agrees with older experimental determinations of this quantity but deviates from potential-model calculations and a more recent result from Black et al, which find larger values around 14 fm [1][2][3][4].…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…A consistent treatment of screening effects is crucial for a stable and reliable theoretical extraction of this quantity. Our result for the quartet pd scattering length, 4 a p-d = (10.9 ± 0.4) fm, agrees with older experimental determinations of this quantity but deviates from potential-model calculations and a more recent result from Black et al, which find larger values around 14 fm [1][2][3][4].…”
Section: Discussionsupporting
confidence: 70%
“…Including a new measurement of the p-d cross section performed at Triangle Universities Nuclear Laboratory (TUNL) for very low proton center-of-mass energies of only 163 and 211 keV, they extracted a value of 4 a p-d = (14.7 ± 2.3) fm. While this falls in line with theoretical extractions of the quantity based on potential-model calculations [2][3][4] that find values for 4 a p-d close to about 13.8 fm (see Table 1 in Ref. [1] for details), it deviates quite significantly from older experimental determinations of 4 a p-d that find values between (11.11 +0.25 −0.24 ) fm [5] and (11.88 +0.4 −0.1 ) fm [6] (cf.…”
Section: Introductionsupporting
confidence: 84%
See 1 more Smart Citation
“…The most recent determination of this quantity, carried out by Black et al [1], extracts a value of 4 a p-d = (14.7 ± 2.3) fm. While this falls in line with theoretical extractions of the quantity based on potential-model calculations [2][3][4] that find values close to about 13.8 fm, it deviates quite significantly from older experimental results for 4 a p-d between 11 and 12 fm [5,6]. In this work, we present a theoretical calculation of 4 a p-d using pionless effective field theory (pionless EFT).…”
Section: Introductionsupporting
confidence: 82%
“…[5] experiment does not indicate an excited state. However, in a recent work [7] it was shown that the effective range function of the doublet d+p scattering has a singularity at a negative energy, just below the d + p threshold. This would indicate the existence of subthreshold virtual states in 3 He.…”
Section: Introductionmentioning
confidence: 98%